Hubungan Antara Self Eficacy Dengan Kecemasan Berbahasa Asing Pada Santri Baru Pondok Pesantren Nahdhatul Muslimat Surakarta - Mardhatillah, Hanifah (2016)
Foreign language anxiety is a concern on an event related to learning a second language after their mother tongue. Foreign language anxiety arising from a psychological factors, namely self-efficacy or self eficacy low against capabilities. Self eficacy own contribution in language learning, especially when applied in everyday conversation. The purpose of this study was to determine the relationship of self eficacy with foreign language anxiety, as well as determine the level of self eficacy and foreign language anxiety level on a new boarding school students Nahdhatul's Women Surakarta. This type of quantitative research, using new students research subjects Nahdhatul Moslem boarding school in Surakarta totaled 55 students. Methods of data collection using psychological scale, the scale of self eficacy and foreign language anxiety scale, with incidental sampling method. While data analysis using product moment correlation. The results showed that there was a significant negative correlation between self eficacy with foreign language anxiety. The higher self eficacy new Santi, the lower the anxiety foreign language, and vice versa the lower the self eficacy a new students, the higher the anxiety foreign language. The level of self eficacy new students cottage NDM (Nahdlatul Moslem) classified as moderate and the level of anxiety in foreign language students cottage NDM moderate. Self eficacy be one that can affect foreign language anxiety.